การศึกษาความพึงพอใจของผู้ร่วมงานต่อการปฏิบัติงานของพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิด - หวังเรืองสถิตย์, รุ่งทิวา; ทองรัตน์, ยุคนธร; วันชัย, อัศนี (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยครั้งนี้เป็นวิจัยเชิงสำรวจเพื่อศึกษาความพึงพอใจของผู้ร่วมงานต่อการปฏิบัติงานของพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิด กลุ่มตัวอย่างเป็นผู้ที่ปฏิบัติงานร่วมกับพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิดที่สำเร็จการอบรมหลักสูตรการพยาบาลเฉพาะทางสาขาเวชปฏิบัติวิกฤตทารกแรกเกิด วิทยาลัยพยาบาลบรมราชชนนี พุทธชินราช จำนวน 295 คน เครื่องมือในการวิจัยได้แก่ แบบสอบถามความพึงพอใจของผู้ร่วมงานต่อการปฏิบัติงานของพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิด สร้างขึ้นจากการทบทวนวรรณกรรม และเอกสารที่เกี่ยวข้อง ลักษณะคำตอบเป็นมาตรส่วนประมาณค่า วิเคราะห์ข้อมูลโดยใช้ความถี่ ร้อยละค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐานผลการวิเคราะห์ข้อมูล พบว่า ค่าเฉลี่ยความพึงพอใจของผู้ร่วมงานต่อการปฏิบัติงานของพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิดโดยรวม และรายด้านอยู่ในระดับมาก โดยด้านความสัมพันธ์ระหว่างบุคคล และความรับผิดชอบในการปฏิบัติงานมีค่าเฉลี่ยสูงที่สุด ( = 4.31, S.D. = 0.53) ด้านบุคลิกภาพในการปฏิบัติงานมีค่าเฉลี่ยต่ำที่สุด ( = 4.09, S.D. = 0.52) ค่าเฉลี่ยด้านรรยาบรรณในการปฏิบัติงาน ด้านความรู้ในการปฏิบัติงาน และด้านทักษะในการปฏิบัติงานเท่ากับ 4.26 (S.D. = 0.52), 4.15 (S.D. = 0.51) และ 4.13 (S.D. = 0.51) ตามลำดับ ผลการวิจัยนำมาใช้เป็นข้อมูลพื้นฐานในการพัฒนาการอบรมหลักสูตรเวชปฏิบัติวิกฤตทารกแรกเกิด และควรมีการศึกษาความพึงพอใจของผู้ที่ได้รับบริการจากพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิด และศึกษาเปรียบเทียบความคิดเห็นต่อการปฏิบัติงานในมุมมองของผู้ร่วมงาน และในมุมมองของพยาบาลเวชปฏิบัติวิกฤตทารกแรกเกิดต่อไป The Study of Colleague’s Atisfaction on Neonatal Critical Care Nurse Practitioner This survey study was conducted to examine colleagues’ satisfaction on neonatal critical care nurse practitioner. The samples were 295 colleagues of neonatal critical care nurse practitioner who are working with neonatal critical care nurse practitioner fnishing neonatal critical care nurse practitioner program from Boromarajonani College of Nursing Buddhachinaraj. The research instrument was a colleagues’ satisfaction on neonatal critical care nurse practitioner questionnaire developed by the researcher. The answers in questionnaire were rating scales. Data were analyzed using frequency, percentage, mean, and standard deviation. The results of this study showed that overall colleagues’ satisfaction on neonatal critical care nurse practitioner mean scores were at high level. The mean scores of these in all aspects were at high level. The highest mean score was interpersonal relationship and responsibility aspect ( = 4.31, S.D. = 0.53). The lowest score was personal aspect ( = 4.09, S.D. = 0.52). The mean scores of moral and professional ethical aspect, knowledge aspect, and accomplishment aspect were 4.26 (S.D. = 0.52), 4.15 (S.D. = 0.51) and 4.13 (S.D. = 0.51), respectively. The fndings of this study suggest that neonatal critical care nurse practitioner program provider should use this result to improve the outcome of this program and forward study about customers’ satisfaction on neonatal critical care nurse practitioner service. Moreover, colleagues and neonatal critical care nurse practitioner view comparison on neonatal critical care nurse practitioner service is explored. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">